Dictionary of Health Economics and Finance. - Marcinko, David Edward (Springer Pub. Co., 2006)
Designated a Doody's Core Title!. "Medical economics and finance is an integral component of the health care industrial complex. Its language is a diverse and broad-based concept covering many other industries: accounting, insurance, mathematics and statistics, public health, provider recruitment and retention, Medicare, health policy, forecasting, aging and long-term care, are all commingled arenas ... The Dictionary of Health Economics and Finance will be an essential tool for doctors, nurses and clinicians, benefits managers, executives and health care administrators, as well as graduat